Can transformational leadership lead to school improvement and school effectiveness? - Muzvidziwa, Irene (Department of Teacher Education (DTE), University of Zimbabwe, 2016)
This article examines the link between transformational leadership and collaborative school cultures, in promoting school improvement arid school effectiveness. The author seeks to highlight the importance of transformational leadership with teachers, parents, and school heads " cooperation as critical factors in school improvement and school effectiveness. The author's main argument is that, transformational leadership can make a difference in terms of school improvement and school effectiveness. This will depend however, on what people value, effective school-community partnership and collaborative leadership. Transformational leadership can be achieved not only in developed countries, but also in third world countries where traditionally, leadership has tended to be hierarchical and autocratic.